Translating an Auditor’s Report: an instance of specialised legal translation - Jan Engberg; Marianne Grove Ditlevsen (JoSTrans: The Journal of Specialised Translation)
In this article we would like to look at the question of why the translation of highly standardised legal texts is at the same time easy (due to the degree of standardisation of the formulations) and difficult (due to the roots of the texts in the national legal culture). The article will be centred on the difficulties stemming from the texts and their contexts and the strategic choices that have to be made when translating an auditor’s report between Danish and English. Translating standardised legal texts may in fact be easy, when the translator has taken the necessary time to make sure s/he is making the right choices.